MANTRA CHANTING WELL-BEING OF MIDDLE AGE PEOPLE - Rao, Puja Dawar; Sharan, Anjali Midha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Vedic mantra chanting has been an integral part of our ancient Indian system. It has been recognized for its profound impact on the overall well-being of humans and plants. Extensive research has been conducted on specific mantras such as OM, Gayathri, and Maha Mrityunjay, highlighting their positive effects on humans including memory, attention, and mental clarity. However, within the gamut of different mantras, the effects of chanting Vishnu Sahasranamam mantra remain largely unexplored. This paper aims to bridge this gap by not only identifying and addressing the limited research available on the Vishnu Sahasranamam mantra’s effects on the overall well-being of people but also tries to understand the effects of chanting these mantras specifically on the middle-aged group which as per Encyclopedia Britannica (2024)i is between the age of 40-60 years. By synthesizing existing literature and proposing avenues for further research, this paper contributes to a deeper understanding of the holistic benefits of various mantra chanting in enhancing overall well-being of humans especially, the middle age group.